A polyurea coating and its preparation method and application
By combining tannic acid with polycoges, a dual -link network structure is formed, and shells of chitosa are introduced, which solves the problem of the unstable and poor anti -pollution resistance of existing coating, and achieves high durability and efficient and efficient Oil and water separation effect.
Patent Information
- Application Number
- CN202410909529.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-08
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-07-08
AI Technical Summary
The existing natural polymer coatings have problems of instability, low durability and poor soil resistance during oil-water separation, and it is difficult to maintain long-term underwater superoleophobicity in complex water environments.
Natural polyphenols that use mussel bionics are combined with polyphonic acid with polyetraphin to form an bionic semicoltaic coating. Through the expansion effect of tannic acid, and the chemical reactions of isocyanate, the physical chemical dual cross -linking network is formed Structure, and introduce a chitosan by pentalhydrolytic aldehyde to form a stable oil and water separation membrane.
It improves the durability and pollution resistance of the coating, enhances the adhesion to the base, is suitable for various complex oil and water separation environments, and realizes efficient oil and water separation.
Smart Images

Figure CN118667422B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new materials and surface technology, and in particular relates to a polyurea coating and a preparation method and application thereof. Background Art
[0002] With the development of industry and the improvement of people's living standards, the demand for oil has increased dramatically, resulting in oily wastewater generated in the process of oil extraction and transportation, industrial wastewater discharge, etc., which is seriously threatening human survival and the surrounding environment. Therefore, people are committed to developing more efficient oil-water separation methods. In recent years, among the many oil-water separation methods, oil-water separation membrane materials with special wettable surfaces have received widespread attention in the field of oil-water separation due to their high separation efficiency, energy saving, environmental protection, and low cost. Among them, natural polymer materials are one of the most commonly used materials for constructing superhydrophilic surfaces. However, due to the instability and low durability of natural polymer coatings, and the fact that oily wastewater often has complex components such as corrosive substances and sediment, in the process of oil-water separation, natural polymer coatings are often difficult to maintain long-term underwater superoleophobicity and lose their oil-water separation ability. On the one hand, most natural polymer coatings have poor mechanical properties and are difficult to withstand long-term scratching during the oil-water separation process. On the other hand, the combination between natural polymer coatings and substrates is often a simple coating method with weak bonding force, and is more likely to fall off in complex water environments. Therefore, the preparation of long-term stable and durable superhydrophilic-underwater superoleophobic coatings remains a challenge.
[0003] China's authorized patent CN110302564B-A kind of oil-water separation material based on nanocellulose / guar gum composite hydrogel and its preparation method and application discloses that nanocellulose and guar gum are used as raw materials, and a hydrogel coating layer is formed on a mesh matrix by using nanocellulose and guar gum through layer-by-layer self-assembly to make a mesh filter material coated with a polymer composite hydrogel. The gelation depends only on non-covalent bonds such as electrostatic interactions. The process is very rapid. After the two substances come into contact, the hydrogel can be instantly completed through layer-by-layer self-assembly to form an oil-water separation material based on nanocellulose / guar gum composite hydrogel. Although the preparation method of this patent is simple, it only has a simple coating method, and it only relies on weak binding forces such as static electricity, which makes it difficult to ensure the durability of the separation material. It is simple and convenient, but it also increases the waste of resources.
[0004] China's authorized patent CN113577826B-polyurethane foam loaded hydrophobic modified peanut shell composite material and its preparation method discloses the use of long carbon chain hexadecyl trimethoxy silane to graft modify the pretreated peanut shell powder; then the hydrophobic modified peanut shell powder is mixed with end isocyanate polyurethane prepolymer and water, and after foaming and curing, a hydrophobic polyurethane foam loaded modified peanut shell powder composite material is obtained. The polyurethane foam / modified peanut shell powder composite material prepared by the present invention has good hydrophobicity, stability and regeneration, and can effectively improve the oil-water separation ability of polyurethane foam, but the hydrophobic coating is easily contaminated by oil on the surface and is not conducive to use. China's authorized patent CN114437402B-a super-hydrophobic polyurethane sponge and its preparation method and application disclose the use of cheap and easily available montmorillonite as raw material, after modification with long-chain carboxylic acid and silane, a suspension of super-hydrophobic material is obtained, and then the polyurethane sponge modified by dopamine hydrochloride is immersed in the suspension to obtain a super-hydrophobic polyurethane sponge. The prepared sponge selectively adsorbs the oil phase and can be used in an oil-water separation device to achieve oil-water separation, with a separation efficiency of more than 99.6%. The sponge prepared by the present invention has strong environmental adaptability, is resistant to friction and corrosion, and does not contain fluorine-containing substances. It is an environmentally friendly material, but similarly, the hydrophobic coating is easily contaminated by oil on the surface and is not conducive to use. The above is the application of polyurea and polyurethane in the field of oil-water separation materials, which are mostly used in the form of foam, sponge, etc. Although the foam form is prepared in a simple foaming form, it is difficult to have good anti-fouling and mechanical properties in the field of oil-water separation. The sponge form mostly exists in the form of a substrate, and has the disadvantages of poor anti-fouling and high energy consumption.
[0005] Membrane separation technology is the most energy-saving, environmentally friendly and efficient of the many existing separation methods. In addition, a water film will be formed during the separation process, which makes it have good anti-fouling properties. Existing solutions mostly use natural polymers and their derivatives to construct special wettable surfaces, which have poor durability. Polyurea and polyurethane materials are mostly used in the form of foam and sponge for oil-water separation, and the separation effect is poor. Summary of the invention
[0006] The purpose of the present invention is to provide a polyurea coating and a preparation method and application thereof.
[0007] In order to solve the problems existing in the prior art, the technical solution adopted by the present invention is:
[0008] In a first aspect, the present invention provides a polyurea coating, which is composed of the following raw materials in the following solid-liquid ratio:
[0009] Polyurea prepolymer: tannic acid: organic solvent: isophorone diisocyanate = 30.47-56.59: 0.66-1.24: 6.64-12.32: 0.62-1.16;
[0010] The polyurea prepolymer is composed of the following raw materials in the following solid-liquid ratio:
[0011] Organic solvent: polyetheramine: isophorone diisocyanate: organotin catalyst = 13.28-24.64: 14-26: 3.11-5.77: 0.013-1.3.
[0012] Furthermore, the organic solvent is dimethylformamide (DMF) or dimethylacetamide.
[0013] Furthermore, the catalyst is dibutyltin dilaurate or stannous octoate.
[0014] Preferably, the polyurea coating is composed of the following raw materials in the following solid-liquid ratio:
[0015] Polyurea prepolymer: tannic acid: organic solvent: isophorone diisocyanate = 43.53: 0.95: 10: 0.89;
[0016] The polyurea prepolymer is composed of the following components in parts by weight:
[0017] Dimethylformamide:polyetheramine:isophorone diisocyanate:organotin catalyst=20:20:4.44:0.13.
[0018] In a second aspect, the present invention provides a method for preparing the polyurea coating according to the first aspect, comprising the following steps:
[0019] ① Add polyetheramine and isophorone diisocyanate to dimethylformamide, then add dibutyltin dilaurate as a catalyst, and stir in a water bath to obtain a polyurea prepolymer;
[0020] ② Dissolve tannic acid in dimethylformamide in advance, then add it to the polyurea prepolymer, add isophorone diisocyanate at the same time, and stir in a water bath to obtain a polyurea coating.
[0021] In a third aspect, the present invention provides a wetted polyurea-based oil-water separation membrane, which is obtained by compounding the polyurea coating described in the first aspect with a substrate.
[0022] Furthermore, the substrate is a metal mesh.
[0023] In a fourth aspect, the present invention provides a method for preparing the impregnated polyurea-based oil-water separation membrane according to the third aspect, comprising the following steps:
[0024] The polyurea coating described in the first aspect is diluted to 10wt% and then coated on a metal mesh, dried in an oven at 70°C, and then immersed in a 1wt%-4wt% glutaraldehyde aqueous solution at 30°C-60°C for 1h-4h. The glutaraldehyde-treated metal mesh is immersed in a CS / HCl aqueous solution for reaction, taken out and rinsed to remove unreacted chemicals, and then placed in deionized water for hydration to obtain an impregnated polyurea-based oil-water separation membrane.
[0025] Preferably, the concentration of the CS / HCl aqueous solution is 1 wt %.
[0026] In a fifth aspect, the present invention provides application of the impregnated polyurea-based oil-water separation membrane described in the third aspect in the field of oil-water separation.
[0027] The advantages and beneficial effects of the present invention are:
[0028] The present invention combines tannic acid, a natural polyphenol substance of mussel biomimetic, with polyurea prepolymer to prepare a biomimetic semi-polyurea coating. Tannic acid is used as a chain extender to combine with polyurea prepolymer to form a physical and chemical double cross-linked network structure, which has both a chemical reaction between isocyanate and hydroxyl and a hydrogen bond between the hydroxyl in tannic acid and the urea bond. The coating is simply and conveniently applied on a substrate such as a metal mesh by brushing. The strong adhesion of tannic acid and the high wear resistance of the polyurea component and the coordination synergy formed between the metal substrate make the coating firmly adhere to the surface of the metal mesh. Chitosan is further introduced by glutaraldehyde, and an oil-water separation membrane can be obtained after hydration. Due to the strong adhesion of the coating and the unique toughness and wear resistance of the polyurea itself, and the introduction of chitosan by chemical bond connection, the separation material shows high durability and is suitable for various complex oil-water separation environments.
[0029] The oil-water separation membrane prepared by the present invention can be used in conjunction with a specific oil-water separator to separate a large amount of oil-water mixture containing complex components such as acids, alkalis and salts.
[0030] The present invention forms a coating layer by brushing a special polyurea coating on a metal mesh between 40-50 microns of aperture, and elements such as nitrogen and oxygen in the coating can form coordination with metal ions, so that the coating is more firmly attached to the substrate surface. Because tannic acid has a polyphenolic hydroxyl structure, it synergizes with other components in the polyurea coating, so that metal elements in the polyurea coating and the metal mesh substrate undergo complexation, and chemically connects with other components in the coating simultaneously, improves substrate adhesion, thereby effectively enhancing coating durability. The introduction of the hydrophilic component chitosan not only includes the mode of chemical bond connection of glutaraldehyde, but also includes the hydrogen bond between chitosan and the polyurea coating, and chitosan is connected to the active site (-OH) of tannic acid by glutaraldehyde, further improving the firmness of its combination.
[0031] The preparation method of the impregnated polyurea-based oil-water separation membrane of the present invention is simple; it can be prepared without high temperature conditions of over 100 degrees, thus saving energy; after the polyurea coating is prepared, it can be stored for standby use, and can be directly applied to a metal mesh when needed, thus being convenient to use. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The infrared FTIR and surface X-ray photoelectron spectroscopy XPS spectra of the samples obtained in each step of Example 5 are shown in FIG. 1 , wherein:
[0033] a is an infrared FTIR spectrum, where OSSW: original stainless steel mesh, SPU: stainless steel mesh coated with polyurea coating, SPUG: SPU treated with glutaraldehyde, SPUC: impregnated polyurea-based oil-water separation membrane treated with chitosan;
[0034] b is the full XPS spectrum of SPUC;
[0035] cf is the spectra of C, O, N, and Fe in the XPS spectrum of SPUC;
[0036] Figure 2 It is the spline tensile mechanical property curve of polyurea (TAPU) and polyurea (ODHPU);
[0037] Figure 3 It is the spline tensile mechanical property curve of chitosan introduced by glutaraldehyde on the basis of polyurea (TAPU);
[0038] Figure 4 It is the separation efficiency diagram of different samples for different oil and water mixtures;
[0039] Among them: SC is prepared by directly placing the stainless steel mesh in a 1wt% CS / HCl aqueous solution for immersion reaction for 12 hours; SPU is prepared by applying a coating diluted to 10wt% by DMF on the stainless steel mesh, without glutaraldehyde and chitosan; SPUC (5%), SPUC (10%), and SPUC (20%) are prepared by applying a coating diluted to 5wt%, 10wt% and 20wt% by DMF, and the remaining steps are the same as Example 5. Figure 4 The results show that different materials have a certain effect on the reaction of different oils and water in a certain ratio (20mL, V oil :V water =1:1) separation efficiency of mixed oil-water mixture. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present application to clearly describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments in the present application belong to the scope of protection of this application.
[0041] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0042] Dimethylformamide (DMF), polyetheramine (D2000), isophorone diisocyanate (IPDI), dibutyltin dilaurate (DBTL), tannic acid (TA), glutaraldehyde, dimethylacetamide (DMAC), oxalyl dihydrazide (ODH), stannous octoate, and chitosan (CS) were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0043] HCL was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0044] Example 1
[0045] This embodiment provides a polyurea coating, which is prepared by the following method:
[0046] First, add 20 ml of dimethylformamide to a three-necked flask, then add 20 g of polyetheramine and 4.44 g of isophorone diisocyanate, and finally add 0.13 g of dibutyltin dilaurate, and stir for 0.5 h in a water bath at 30 ° C to obtain a polyurea prepolymer; dissolve 0.95 g of TA in 10 ml of DMF in advance, then add it to 43.53 g of polyurea prepolymer, and add 0.89 g of IPDI at the same time, stir for 3.5 h in a water bath at 50 ° C to obtain a polyurea coating. The polyurea coating is stored in a sealed state at room temperature for later use.
[0047] Example 2
[0048] This embodiment provides a polyurea coating, which is prepared by the following method:
[0049] First, add 24.64 ml of dimethylformamide into a three-necked flask, then add 14 g of polyetheramine and 3.11 g of isophorone diisocyanate, and finally add 0.013 g of dibutyltin dilaurate, and stir for 0.5 h in a water bath at 30 ° C to obtain a polyurea prepolymer; dissolve 1.24 g of TA in 6.64 ml of DMF in advance, and then add it to 30.47 g of polyurea prepolymer, and add 0.62 g of IPDI at the same time, and stir for 3.5 h in a water bath at 50 ° C to obtain a polyurea coating.
[0050] Example 3
[0051] This embodiment provides a polyurea coating, which is prepared by the following method:
[0052] First, add 13.28 ml of dimethylformamide into a three-necked flask, then add 26 g of polyetheramine and 5.77 g of isophorone diisocyanate, and finally add 1.3 g of dibutyltin dilaurate, and stir in a water bath at 30 ° C for 0.5 h to obtain a polyurea prepolymer; dissolve 0.66 g of TA in 12.32 ml of DMF in advance, and then add it to 56.59 g of polyurea prepolymer, and add 1.16 g of IPDI at the same time, and stir in a water bath at 50 ° C for 3.5 h to obtain a polyurea coating.
[0053] Example 4
[0054] This embodiment provides a polyurea coating. The only difference between this embodiment and embodiment 1 is that dimethylacetamide is used instead of dimethylformamide, and stannous octoate is used instead of dibutyltin dilaurate. The rest is the same as embodiment 1.
[0055] Comparative Example 1
[0056] This comparative example provides a polyurea coating. The only difference between this comparative example and Example 1 is that oxalyl dihydrazide (ODH) is used instead of tannic acid (TA) as a chain extender, and the rest is the same as Example 1.
[0057] Comparative Example 2
[0058] This comparative example provides a polyurea coating. The difference between this comparative example and Example 1 is only that 2g of tannic acid is added, and the rest is the same as Example 1.
[0059] Example 5
[0060] This embodiment provides a wetted polyurea-based oil-water separation membrane, and the preparation method thereof comprises the following steps:
[0061] ① First, use ethanol and deionized water to ultrasonically clean the stainless steel mesh with a pore size between 40 and 50 microns for 20 minutes, and then dry it in an oven at 70°C for use.
[0062] ② The polyurea coating prepared in Example 1 was diluted to 10wt% with DMF, and the diluted coating was applied once on the stainless steel mesh using a 1cm wide brush, and then dried in an oven at 70°C to obtain a stainless steel mesh coated with a polyurea coating; then the stainless steel mesh coated with the polyurea coating was immersed in a 2.5wt% glutaraldehyde aqueous solution at 40°C for 3h; and a stainless steel mesh coated with a polyurea coating treated with glutaraldehyde was obtained.
[0063] ③ Dissolve chitosan in 0.1 mol / L HCl aqueous solution to obtain a 1 wt% CS / HCl aqueous solution, place the glutaraldehyde-treated stainless steel mesh in the CS / HCl aqueous solution for immersion reaction for 12 hours, take it out and rinse it with a large amount of deionized water to remove the unreacted chemicals, then put it in deionized water for hydration for 24 hours to obtain an infiltrated polyurea-based oil-water separation membrane.
[0064] Figure 1 Infrared FTIR and surface X-ray photoelectron spectroscopy XPS spectra of the original stainless steel mesh used in this Example 5, the stainless steel mesh coated with polyurea coating obtained in step ②, the stainless steel mesh coated with polyurea coating treated with glutaraldehyde, and the sample impregnated with polyurea-based oil-water separation membrane obtained in step ③.
[0065] according to Figure 1 a shows that 3356cm in SPU -1 The broad peaks near the tannic acid represent the stretching vibrations of -OH and -NH, mainly the remaining -OH in tannic acid, and -NH from the urea bond at 2921 cm -1 There is an obvious -CH3 stretching vibration absorption peak at 1674cm -1 、1490cm -1 and 1243cm -1 The C=O, NH, and CN appearing at 1092 cm -1 The CO stretching vibration absorption peak at is attributed to the connection between tannic acid and polyurea prepolymer and D2000. In glutaraldehyde treatment (SPUG), the introduction of glutaraldehyde further reduced -OH, resulting in a slightly weaker peak. In SPUC, the introduction of chitosan led to a large increase in -OH, resulting in a stronger peak. At the same time, the presence of -NH2 in chitosan slightly strengthened the NH and CN peaks.
[0066] according to Figure 1 b It can be seen that in the XPS full spectrum of SPUC, in addition to various metal elements in the metal substrate, there are C1s, O1s, and N1s signals at 284.97eV, 531.93eV, and 399.27eV, and these elements all come from the polyurea / chitosan composite coating.
[0067] according to Figure 1 c It can be seen that (the CC peak is at 284.80eV, the appearance of the CN (286.37eV) peak is attributed to the formation of urea bonds and the introduction of chitosan, the appearance of the CO (287.95eV) peak is also attributed to the connection between tannic acid and polyurea prepolymer and D2000, and the C=O (288.94eV) peak is attributed to the generation of urea bonds.).
[0068] according to Figure 1d It can be seen that (the C-OH (532.32 eV) peak is attributed to the remaining -OH in tannic acid and the -OH in chitosan, and the origin of the O=C (532.85 eV) peak and the OC (534.31 eV) peak corresponds to the C1s spectrum).
[0069] according to Figure 1 e It can be seen that (the NC (400.00 eV) peak and the NH (401.89 eV) peak are attributed to the formation of urea bonds and the introduction of chitosan).
[0070] according to Figure 1 f shows that the proportion of Fe(Ⅱ) is significantly higher than that of Fe(Ⅲ), indicating that only a small amount of Fe(Ⅱ) is oxidized in the stainless steel mesh.
[0071] Example 6
[0072] This embodiment provides a wetted polyurea-based oil-water separation membrane. The only difference between this embodiment and embodiment 5 is that the polyurea coating prepared in embodiment 2 is used, and the rest is the same as embodiment 5.
[0073] Example 7
[0074] This embodiment provides a wetted polyurea-based oil-water separation membrane. The only difference between this embodiment and embodiment 5 is that the polyurea coating prepared in embodiment 3 is used, and the rest is the same as embodiment 5.
[0075] Example 8
[0076] This embodiment provides a wetted polyurea-based oil-water separation membrane. The only difference between this embodiment and embodiment 5 is that the polyurea coating prepared in embodiment 4 is used, and the rest is the same as embodiment 5.
[0077] Comparative Example 3
[0078] This comparative example provides a wetted polyurea-based oil-water separation membrane. The difference between this comparative example and Example 5 is only that the polyurea coating prepared in Comparative Example 1 is used, and the rest is the same as Example 5.
[0079] Comparative Example 4
[0080] This comparative example provides a wetted polyurea-based oil-water separation membrane. The difference between this comparative example and Example 5 is only that the polyurea coating prepared in Comparative Example 2 is used instead of the polyurea coating prepared in Example 1, and the rest is the same as Example 5.
[0081] Comparative Example 5
[0082] This comparative example provides a wetted polyurea-based oil-water separation membrane. The only difference between this comparative example and Example 5 is that a sodium carboxymethyl cellulose (CMC) aqueous solution is used instead of a CS / HCl aqueous solution. The rest is the same as Example 5.
[0083] Experimental example
[0084] The separation performance, mechanical properties and stability of the impregnated polyurea-based oil-water separation membranes prepared in Examples 5-8 and Comparative Examples 3-5 were measured.
[0085] 1. Separation performance
[0086] Each group used two syringe plastic tubes and two metal binder clips to form an oil / water mixture separation device. The impregnated polyurea-based oil / water separation membranes prepared in Examples 5-8 and Comparative Examples 3-5 were completely wetted with water and placed between the two tubes and fixed with binder clips. Toluene, gasoline, n-hexane, diesel, kerosene and petroleum ether were dyed with Oil Red O and mixed with water in a ratio of (20 mL, V oil :V water =1:1) to prepare a variety of oil / water mixtures. The separation process is to pour an oil / water mixture into the upper tube and separate it by gravity. The water passes through the material while the oil is blocked above the material. The experimental results are shown in Table 1:
[0087] Table 1 Separation performance of wetted polyurea-based oil-water separation membrane
[0088]
[0089] According to Table 1, the separation efficiency of the impregnated polyurea-based oil-water separation membranes prepared in Examples 5-8 for the six kinds of oils is better than that of all the comparative examples, among which Example 5 has the best effect. The separation efficiency of the impregnated polyurea-based oil-water separation membranes prepared in Example 5 for the six kinds of oils is all above 98%, and the separation flux for the six kinds of oils is all 8815.01 L / m 2 / h or more.
[0090] In Comparative Example 3, since oxalyl dihydrazide is used instead of tannic acid as the chain extender, there is no phenolic hydroxyl group, and the coating cannot be firmly attached to the surface of the metal mesh. The reduction of hydroxyl groups leads to a decrease in the hydrophilicity of the material, resulting in a significant decrease in the separation efficiency of the six oils.
[0091] In Comparative Example 4, due to the excessive amount of tannic acid used, the cross-linking degree of polyurea was greatly enhanced, resulting in a significant decrease in the separation efficiency and separation flux of the six oils.
[0092] In Comparative Example 5, since sodium carboxymethyl cellulose aqueous solution is used instead of CS / HCl aqueous solution, there is no amino group in sodium carboxymethyl cellulose, which is difficult to connect with glutaraldehyde under normal conditions, resulting in a decrease in the separation efficiency and separation flux of the six oils. This may be because the present application introduces chitosan by chemical bond connection, making the separation material show high durability.
[0093] 2. Mechanical properties:
[0094] The polyurea coating in Example 1 was filled into a polytetrafluoroethylene mold and dried at 70 degrees Celsius to obtain polyurea (TAPU).
[0095] The polyurea coating in Comparative Example 1 was filled into a polytetrafluoroethylene mold and dried at 70 degrees Celsius to obtain polyurea (ODHPU).
[0096] Polyurea (TAPU) and polyurea (ODHPU) were prepared into polyurea dumbbell-shaped specimens, and the polyurea dumbbell-shaped specimens were stretched using a universal material testing machine (refer to GB / T528-2009). The initial distance between the clamps was 33 mm and the stretching speed was 30 mm / min. The corresponding force and displacement curves were obtained and the test was repeated 3 times. The stress-strain curves were obtained as shown in the following figure. Figure 2 shown.
[0097] according to Figure 2 It can be seen that compared with polyurea (TAPU) and polyurea (ODHPU), the tensile stress of polyurea (TAPU) is 3.02MPa, the tensile strain is 775.47%, and the tensile stress of polyurea (ODHPU) is 1.96MPa, the tensile strain is 458.32%. It can be seen that the tensile mechanical properties of polyurea (TAPU) are much better than those of polyurea (ODHPU).
[0098] According to the method described in Example 5, in the absence of a metal substrate, a polyurea-based composite membrane (TAPU-CS) was prepared by introducing chitosan into polyurea (TAPU) by glutaraldehyde.
[0099] according to Figure 3 It can be seen that the tensile stress of the polyurea-based composite film (TAPU-CS) is 3.24 MPa and the tensile strain is 797.73%. It can be seen that the introduction of chitosan slightly enhances the tensile mechanical properties of polyurea (TAPU).
[0100] The adhesion of the polyurea film to the stainless steel substrate was tested using a pull-off adhesion tester (refer to GB / T5210-2006). The polyurea coatings prepared in Examples 1-4 and Comparative Examples 1-2 were directly brushed on the stainless steel plate, respectively, with a coating thickness of 0.1 mm, and the excess solvent was evaporated to obtain a polyurea coating. The spindle diameter used in the experiment was 10 mm, and the coating failure mode was coating-substrate interface failure. The maximum tensile force and adhesion that the coating can withstand were obtained, and the test results are shown in Table 2.
[0101] Table 2
[0102] Mean stress Average strain Maximum tensile force that the coating can withstand Adhesion Example 1 3.02MPa 775.47% 411.34N 5.24Mpa Example 2 2.83MPa 559.92% 385.65N 5.01Mpa Example 3 2.36MPa 583.64% 342.26N 4.76Mpa Example 4 2.85MPa 659.15% 365.31N 4.88Mpa Comparative Example 1 1.96MPa 458.32% 286.48N 3.54Mpa Comparative Example 2 1.85MPa 472.69% 265.34N 3.29Mpa
[0103] According to Table 2, the maximum tensile force and adhesion of the polyurea coatings prepared in Examples 1-4 are much better than those in Comparative Examples 1 and 2, wherein the maximum tensile force of Example 1 reaches 411.34 N, and the adhesion reaches 5.24 MPa.
[0104] 3. Stability:
[0105] HCl and NaOH were used to prepare aqueous solutions with different pH values, pH = 1, 3, 5, 7, 9, 11, 13, and NaCl was used to prepare a 3wt% NaCl aqueous solution to simulate seawater. The test materials were immersed in the above solutions for 8 hours, and their contact angles and corrosive solution separation efficiency were measured using toluene stained with Oil Red O, and the surface corrosion was observed using SEM. The test results are shown in Table 3. Table 3
[0106]
[0107] As shown in Table 3, the underwater toluene contact angles of the impregnated polyurea-based oil-water separation membranes prepared in Examples 5-8 are all greater than those of Comparative Examples 3-5, among which Example 5 is the best, and the underwater toluene contact angle of the impregnated polyurea-based oil-water separation membrane prepared therefrom reaches above 151.7°. The separation efficiency of the impregnated polyurea-based oil-water separation membranes prepared in Examples 5-8 for corrosive solutions is better than that of Comparative Examples 3-5, among which the separation efficiency of the impregnated polyurea-based oil-water separation membrane prepared in Example 5 for corrosive solutions reaches above 97.5%.
[0108] The physical stability of the impregnated polyurea-based oil-water separation membrane prepared in Examples 5-8 and Comparative Examples 3-5 was tested. The membrane was fixed at the bottom of a conical flask, 5 wt% of 110 mesh fine sand was added, and the surface was scoured and scratched at room temperature using a constant temperature incubator at a speed of 200 r / min to simulate a sandy water environment, and the contact angle after a long time of 180 min of scratching was tested. To further test its physical and mechanical stability, a 200 g weight was used to press it on a 1000 Cw sandpaper, and tweezers were used to push it 10 cm at a time. The underwater toluene contact angle after scratching was measured every 10 times as a cycle, and the contact angle after 50 scratches was tested. The test results are shown in Table 4.
[0109] Table 4
[0110] Physical stability Physical and mechanical stability Example 5 150.8° 147.6° Example 6 148.4° 144.3° Example 7 145.6° 140.8° Example 8 149.3° 146.2° Comparative Example 3 126.3° 117.5° Comparative Example 4 130.7° 123.9° Comparative Example 5 134.6° 131.7°
[0111] The test results show that the contact angle of the wet polyurea-based oil-water separation membrane prepared in Examples 5-8 can still be maintained above 145° after a long scraping time of 180 minutes. However, the contact angle of the wet polyurea-based oil-water separation membrane prepared in Comparative Examples 3-6 can only be maintained at 134.6° at most after a long scraping time of 180 minutes.
[0112] The wet polyurea-based oil-water separation membrane prepared in Example 5-8 was pressed on 1000Cw sandpaper with a 200g weight, and pushed with tweezers for 10cm each time. The underwater toluene contact angle after scratching was measured every 10 times. After 50 times of scratching, the contact angle was still maintained above 140.8°. The wet polyurea-based oil-water separation membrane prepared in Comparative Examples 3-5 could only maintain a contact angle of 131.7° at most.
[0113] The embodiments of the present application are described above in conjunction with the accompanying drawings, but the present application is not limited to the above-mentioned specific implementation methods. The above-mentioned specific implementation methods are merely illustrative and not restrictive. Under the guidance of the present application, ordinary technicians in this field can also make many forms without departing from the purpose of the present application and the scope of protection of the claims, all of which are within the protection of the present application.
Claims
1. A polyurea coating, characterized in that: It is composed of the following raw materials in the following solid-liquid ratio: Polyurea prepolymer: tannic acid: dimethylformamide: isophorone diisocyanate = 43.53: 0.95: 10: 0.89; The polyurea prepolymer is composed of the following raw materials in the following solid-liquid ratio: Dimethylformamide:polyetheramine:isophorone diisocyanate:dibutyltin dilaurate=20:20:4.44:0.
13.
2. The method for preparing the polyurea coating according to claim 1, characterized in that: The following steps are involved: ① Add polyetheramine and isophorone diisocyanate to dimethylformamide, then add dibutyltin dilaurate as a catalyst, and stir in a water bath to obtain a polyurea prepolymer; ② Dissolve tannic acid in dimethylformamide in advance, then add it to the polyurea prepolymer, add isophorone diisocyanate at the same time, and stir in a water bath to obtain a polyurea coating.
3. A method for preparing a wet polyurea-based oil-water separation membrane, characterized in that: The following steps are involved: The polyurea coating of claim 1 is diluted to 10wt% and then coated on a metal mesh, dried in an oven at 70°C, and then immersed in a 1wt%-4wt% glutaraldehyde aqueous solution at 30°C-60°C for 1h-4h, and the glutaraldehyde-treated metal mesh is immersed in a chitosan / HCl aqueous solution for reaction, taken out and rinsed to remove unreacted chemicals, and then placed in deionized water for hydration to obtain an impregnated polyurea-based oil-water separation membrane.
4. The method for preparing a wet polyurea-based oil-water separation membrane according to claim 3, characterized in that: The concentration of the chitosan / HCl aqueous solution is 1 wt %.
5. A wetted polyurea-based oil-water separation membrane, characterized in that: The method is prepared by the method of claim 3 or 4.
6. Use of the impregnated polyurea-based oil-water separation membrane according to claim 5 in the field of oil-water separation.
Citation Information
Patent Citations
An oil-water separation material based on nanocellulose / guar gum composite hydrogel, its preparation method and application
CN110302564B
Polyurethane foam-loaded hydrophobically modified peanut shell composite material and its preparation method
CN113577826B
A superhydrophobic polyurethane sponge, its preparation method and application
CN114437402B